2022
DOI: 10.3390/e24070922
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Exergy Loss of Ammonia Addition in Hydrocarbon Diffusion Flames

Abstract: In this paper, a theoretical numerical analysis of the thermodynamics second law in ammonia/ethylene counter-flow diffusion flames is carried out. The combustion process, which includes heat and mass transfer, as well as a chemical reaction, is simulated based on a detailed chemical reaction model. Entropy generation and exergy loss due to various reasons in ammonia/ethylene and argon/ethylene flames are calculated. The effects of ammonia addition on the thermodynamics efficiency of combustion are investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is obvious that this analytical method is better suited to the practical industrial furnace situation. Therefore, this approach was applied to various problems of thermodynamic analysis of high-temperature systems including 1-D high-temperature systems with participating medium including CO 2 , H 2 O, even soot [ 14 , 15 ], lab-scale hydrocarbon diffusion flames [ 16 , 17 , 18 ], as well as practical combustion facilities [ 19 , 20 , 21 ]. During the above studies, it was found that the thermodynamic role of thermal radiation in the combusting flows should be paid more attention, and the variation in temperature and radiative properties in combustion chambers would have crucial effects on REG.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that this analytical method is better suited to the practical industrial furnace situation. Therefore, this approach was applied to various problems of thermodynamic analysis of high-temperature systems including 1-D high-temperature systems with participating medium including CO 2 , H 2 O, even soot [ 14 , 15 ], lab-scale hydrocarbon diffusion flames [ 16 , 17 , 18 ], as well as practical combustion facilities [ 19 , 20 , 21 ]. During the above studies, it was found that the thermodynamic role of thermal radiation in the combusting flows should be paid more attention, and the variation in temperature and radiative properties in combustion chambers would have crucial effects on REG.…”
Section: Introductionmentioning
confidence: 99%